2014
DOI: 10.1155/2014/549747
|View full text |Cite
|
Sign up to set email alerts
|

Association between eNOS 4b/a Polymorphism and the Risk of Diabetic Retinopathy in Type 2 Diabetes Mellitus: A Meta-Analysis

Abstract: Many studies have assessed the association between eNOS-4b/a polymorphism and the risk of diabetic retinopathy (DR) among type 2 diabetic subjects. However, the results are inconsistent. In order to derive a more precise estimation of the association, a meta-analysis was conducted. Fifteen studies with 3, 183 cases and 3, 410 controls were enrolled by searching the databases of Pubmed, Embase, China National Knowledge Infrastructure (CNKI), and Chinese Wanfang Database. Summary odds ratios (ORs) with 95% confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
3
13
1
1
Order By: Relevance
“…Since it was characterized in the mid-1990s, many polymorphic sites have been described in the human NOS3 gene, including the selected VNTR. However, previous studies on the association between rs869109213 and the risk for DR among T2DM patients reported conflicting and inconclusive results, which might be due to interethnic differences in the distribution of NOS3 polymorphisms [14,19]. Here we confirmed an association between the 4a4a homozygotes of rs869109213 and the occurrence of DR in Slovenian (Caucasians) patients with T2DM.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Since it was characterized in the mid-1990s, many polymorphic sites have been described in the human NOS3 gene, including the selected VNTR. However, previous studies on the association between rs869109213 and the risk for DR among T2DM patients reported conflicting and inconclusive results, which might be due to interethnic differences in the distribution of NOS3 polymorphisms [14,19]. Here we confirmed an association between the 4a4a homozygotes of rs869109213 and the occurrence of DR in Slovenian (Caucasians) patients with T2DM.…”
Section: Discussionsupporting
confidence: 79%
“…Several other authors reported the association between the NOS3 rs869109213 and DR in Caucasians with T2DM [19,21]. For example, Cheema et al [21] found that the 4a4a genotype of rs869109213 was an independent protective factor for DR and was associated with a low risk of DR.…”
Section: Discussionmentioning
confidence: 99%
“…The NOS3 gene is located on chromosome 7q 35–36, and has 26 exons that span more than 21 kb of the genome . In recent years, the human NOS3 gene has been considered as a candidate gene for mediating the susceptibility to T2DM, and the association of several NOS3 genetic polymorphisms (such as rs1799983, a 27‐bp repeat in intron 4, and rs2070744) with the susceptibility to T2DM have been assessed . In our present research, NOS3 rs3918188 genetic polymorphism was significantly associated with the increased susceptibility to T2DM in the homozygote comparison and recessive model.…”
Section: Discussionsupporting
confidence: 49%
“…The eNOS gene is located on chromosome 7q35-36 and includes 26 exons, spanning 21 kb (Ma et al, 2014b). Nitric oxide (NO) is produced as a result of the oxidation of L-arginine by eNOS (Moncada and Higgs, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated ROS production and reduced NO bioavailability, together with the intermediate product peroxynitrite, significantly account for apoptosis in the endothelial cells, and endothelial dysfunction in T2DM (Johansen et al, 2005). The presence of polymorphisms in eNOS might contribute to a decrease in eNOS activity, reduction in the NO level, and has been reported as a potential factor affecting the pathogenesis and development of T2DM (Ma et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%